The Ability of Exercise-Associated Oxidative Stress to Trigger Redox-Sensitive Signalling Responses - Richard Webb; Michael G. Hughes; Andrew W. Thomas; Keith Morris (MDPI AG, 2017)
In this review, we discuss exercise as an oxidative stressor, and elucidate the mechanisms and downstream consequences of exercise-induced oxidative stress. Reactive oxygen species (ROS) are generated in the mitochondria of contracting skeletal myocytes; also, their diffusion across the myocyte membrane allows their transport to neighbouring muscle tissue and to other regions of the body. Although very intense exercise can induce oxidative damage within myocytes, the magnitudes of moderate-intensity exercise-associated increases in ROS are quite modest (~two-fold increases in intracellular and extracellular ROS concentrations during exercise), and so the effects of such increases are likely to involve redox-sensitive signalling effects rather than oxidative damage. Therefore, the responses of muscle and non-muscle cells to exercise-associated redox-sensitive signalling effects will be reviewed; for example, transcription factors such as Peroxisome Proliferator Activated Receptor-gamma (PPARγ) and Liver X-Receptor-alpha (LXRα) comprise redox-activable signalling systems, and we and others have reported exercise-associated modulation of PPARγ and/or LXRα-regulated genes in skeletal myocyte and in non-muscle cell-types such as monocyte-macrophages. Finally, the consequences of such responses in the context of management of chronic inflammatory conditions, and also their implications for the design of exercise training programmes (particularly the use of dietary antioxidants alongside exercise), will be discussed.